Des « craintes légitimes » aux « craintes irrationnelles » : analyse argumentative de l’inscription des modalités appréciatives dans les textes du débat public sur les nanotechnologies - Assimakis Tseronis (Discours)
This paper studies the way in which evaluative modality is used in argumentative discourse. The aim is to identify the strategic effect of the various linguistic realisations of evaluative modality in two argumentative moves, namely the move of advancing a standpoint and the move of advancing arguments in support of the standpoint. This effect depends on the distinct function that each of these moves plays in a debate. As a case in point, the strategic effect of evaluative modality is studied in a corpus of 51 texts produced by various stakeholders during the public debate on nanotechnology in France held between 2009 and 2010.